Проривні технології фінансового менеджменту використання капіталу в контексті стабілізації національної економіки - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Чоловський, Денис; Cholovskyi, Denys (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2022)
У статті визначено сутність проривних технологій в управлінні капіталом підприємства. Сутність проривних технологій в управлінні капіталом підприємства проявляється через циклічний зв'язок впровадження проривних технологій у технологічні цикли підприємств та їх подальшої інтеграції до систем управління. Охарактеризовано переваги та ризики використання проривних технологій для управління капіталом підприємства. Констатовано, що специфічні переваги впровадження проривних технологій лежать у царині автоматизації аналітичної та управлінської діяльності, тоді як недоліки визначаються суб'єктивними недосконалостями інформаційного забезпечення та когнітивного навантаження. Сформульовано напрями трансформації фінансового механізму управління капіталом з урахуванням впровад-ження проривних технологій (трансформації систем регулювання фінансової діяльності підприємств, зовнішньої підтримки фінансової діяльності, фінансових методів, важелів та інструментів). Відповідно донапрямів трансформації фінансового механізму управління капіталом визначено властивості його формування та вибору стратегії управління. The purpose of the article is to characterize the content of breakthrough technologies in enterprise capitalmanagement and the corresponding transformations of the enterprise's financial management system.Research methodology. When writing the article, a set of general scientific and specific methods of economicresearch was used, in particular methods of abstraction (when determining the essence of breakthroughtechnologies and their impact on the transformation of enterprise management systems), analysis (whenstudying the positive and negative effects of breakthrough technologies in the management of enterprise capital,identifying specific features capital management of enterprises that use breakthrough technologies, the choiceof development strategies by such enterprises).The essence of breakthrough technologies in enterprise capital management is determined. The essence ofbreakthrough technologies in enterprise capital management is manifested through the cyclic connection ofthe introduction of breakthrough technologies into the technological cycles of enterprises and their subsequentintegration into management systems. The advantages and risks of using breakthrough technologies forenterprise capital management are characterized. It was established that the specific advantages of theintroduction of breakthrough technologies lie in the field of automation of analytical and managerial activities,while the disadvantages are determined by subjective imperfections of information provision and cognitive load.The directions of the transformation of the financial mechanism of capital management are formulated, taking into account the introduction of breakthrough technologies (transformation of systems for regulating the financialactivity of enterprises, external support of financial activity, financial methods, levers and tools). In accordancewith the directions of transformation of the financial mechanism of capital management, the properties of itsformation and the choice of a management strategy are determined.The scientific novelty of the research results lies in the development of the conceptual foundations of theconstruction of the financial management system of the enterprise's capital based on the use of modernbreakthrough technologies, taking into account the trends of their further development by clarifying the contentof breakthrough technologies in capital management, clarifying the advantages and disadvantages of theirintroduction into the management process, characteristics of the process properties capital formation with theintroduction of breakthrough technologies and the choice of a management strategy.The practical significance of the research results lies in the formation of scientific and practical foundationsfor the introduction of breakthrough technologies in the processes of financial management of the capital ofenterprises with a significant improvement in the efficiency of its use.
Breakthrough techn ologies of financial management of the use of capitalin th e context of stabilizing the n ational economy
Keywords: капітал підприємства; enterprise capital; проривні технології; breakthrough technologies; фінансовий менеджмент; financial management; механізм управління; management mechanism; стратегія розвитку підприємства; enterprise development strategy